Analisis Morfologis terhadap Imbuhan Derivasi pada Pidato Hillary Clinton serta Implikasinya terhadap Pengajaran Bahasa Inggris - Siska Bochari; Hastini Hastini (Jurnal Kreatif Online, 2022)
The purpose of this study is to find and classify the most dominant type and function of derivational affixes in Hillary Clinton’s speech. This study used a qualitative descriptive design. The data of this research are taken from speech that comes from mass media and non-verbal form. The result of the analysis shows that the most dominant type of derivational affixes in Hillary Clinton’s speech is the suffix –ing (97%) and the most dominant function of derivational affix is to form noun (63%) which attached to the root/base of the verb. The implication of this research is that the research result is useful to enrich the theory of morphological analysis of complex words so that the process of word formation becomes easier for non-native speakers.